COMPATIBILITY TESTING OF GUAR GUM WITH METFORMIN HYDROCHLORIDE - PRIYANKA; D N MISHRA (International Journal of Pharma and Bio Sciences, 2013)
Guar gum has gained immense importance because of its constructive role of releasing sugars and absorbing sugars slowly in the intestinal tract; consequently, reduce the severity of diabetes mellitus and also act as a prospective hydrophilic matrix carrier for oral controlled delivery of drugs. Metformin hydrochloride is an oral antidiabetic drug and first-line drug of choice for the treatment of type 2 diabetes, in particular, in overweight and obese people. In this study, an approach to possible physical interaction between metformin hydrochloride and guar gum is presented. For the investigative purpose; molecular level property, particulate level property and thermal methods of analysis have been assessed. Results of FTIR, PXRD and DSC studies indicated that Guar gum had compatibility with Metformin hydrochloride